TAYLOR SWIFT’S COUNTER-NARRATIVE STRATEGIES IN RECLAIMING FEMALE AGENCY IN THE LIFE OF A SHOWGIRL - Jonathan Irene Sartika Dewi Max; Yofi Irvan Vivian (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study is among the first to analyze agency through clause-level transitivity in Swift’s lyrics. This study applies a feminist stylistic framework, supported by Systemic Functional Linguistics (SFL), to analyze lyrics from her 12th album, The Life of a Showgirl, as a counter-narrative resisting patriarchal master plots. The analysis comprised three stages: clause segmentation and coding, discovery of linguistic patterns via quantitative and qualitative methods, and interpretation of these patterns to elucidate themes of agency and identity. The findings demonstrate that agency is constructed through a strategic foregrounding of the Actor in material processes, reframing identity in articulated cognition through mental processes, and introspecting the external constraints through mental processes. These techniques are central to the making of counter narrative and underscore Swift's innovative reassertion of discursive authority. The developed self-narrative is contesting gendered power dynamics and affirming epistemic independence. Findings advance feminist stylistics by showing how linguistic form becomes a locus of resistance.